Nauczyciel prawa wobec problemu nauczania o sprawiedliwości - Zoll, Fryderyk (Horyzonty Wychowania, 2017)
Teachingstudentsoflawaboutjusticeisasubject,whichcan be easily turned into a philosophical dispute about the relation between justice and positive law. This kind of a very theoretical disputemaybeusefulbutitsrealimpactonfuturelegalpractice andfunctioningofthesocietyisquitelimited.Better effects may beachievedthroughtakingbytheacademiamoreresponsibility for the practical education of prospective lawyers. During the earlystagesofeducationstudentsneedtobefacedwiththereal problemsoflifewhichneedtobesolved.TheEuropeanteaching traditionwasmorefocusedonthe„blackletter” of law. This way ofteachingeasilyskipsoutthenecessaryreflectiononthereality ofthelegalpracticeaswellasethicalandjusticeissuesinvolved in it. In the paper, I try to argue that a useful remedy on a very practicallevel is a program of the clinical legal education. In the frames of this academic program, students, supervised by professors, provide a sort of legal assistance to the poor. This programisaccompaniedbyeducationalseminarsandconsulta tions and helps students not only to reflect on how client’s problems can be solved in reality, not only in the formally, but also in the substantially correct way. This problem-solving approach shows the natural limits of the legal system and the need of a broader perspective on the client’s problem. Clinical legal education, by facing students with the problems of poor people, makes the future lawyer more aware of the social problemsinthesociety and the malfunctioning of the legal system. It is a very optimistic sign in Polish legal education that clinical legal education is gradually becoming an education standard among Polish law schools.